2009
DOI: 10.1080/13576500802362927
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of brain asymmetry in the perception of positive and negative facial expressions

Abstract: The divided visual field technique was used to investigate the pattern of brain asymmetry in the perception of positive/approach and negative/withdrawal facial expressions. A total of 80 undergraduate students (65 female, 15 male) were distributed in five experimental groups in order to investigate separately the perception of expressions of happiness, surprise, fear, sadness, and the neutral face. In each trial a target and a distractor expression were presented simultaneously in a computer screen for 150 ms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
60
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 39 publications
12
60
4
1
Order By: Relevance
“…Alves, Aznar-Casanova, & Fukusima, (2009) found faster responses to LVF presentations only for happy and fearful faces but not for sad and surprise stimuli. However, the authors interpreted their finding as support for the Right Hemisphere Hypothesis (Alves et al, 2009). Likewise, a series of other studies, found faster responses and/or higher accuracy for the perception of emotional faces presented to the LVF.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Alves, Aznar-Casanova, & Fukusima, (2009) found faster responses to LVF presentations only for happy and fearful faces but not for sad and surprise stimuli. However, the authors interpreted their finding as support for the Right Hemisphere Hypothesis (Alves et al, 2009). Likewise, a series of other studies, found faster responses and/or higher accuracy for the perception of emotional faces presented to the LVF.…”
Section: Introductionmentioning
confidence: 93%
“…Several of these VHF studies have shown results favoring the Right Hemisphere model in facial emotion perception (Alves et al, 2009;Buchtel et al, 1978;Hugdahl et al, 1989Hugdahl et al, , 1993McKeever & Dixon, 1981;McLaren & Bryson, 1987;Landis et al, 1979;Ley & Bryden, 1979;Safer, 1981;Strauss & Moscovitch, 1981;Suberi & McKeever, 1977). Specifically, Safer (1981) revealed higher accuracy rates for recognizing facial emotions presented in the left visual field (LVF) using the six basic emotions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations